Botulinum toxin in bruxism treatment - Piotr Piech; Hanna Sudzińska; Justyna Pietrak; Maciej Kozioł; Monika Maślanko; Karolina Wilczyńska; Jadwiga Kozioł; Robert Łuczyk (Journal of Education, Health and Sport, 2017)
Introduction: Bruxism is defined as abnormal, fixed, unconscious chewing organ function, deviating qualitatively and quantitatively from normal function. Another definition speaks of motor dysfunction in the mouth, characterized by grinding and clenching of the teeth, occurring during sleep. The etiology of this disorder has not been explained until now, but it is believed to be related to localized, mental, nervous and neurotransmitter disorders.